2021
DOI: 10.1002/brb3.2461
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and attitude of first‐year medical students toward epilepsy in University of Khartoum, Sudan

Abstract: Purpose: Very little is known about the knowledge and attitude of students about epilepsy at Sudanese universities. Therefore, we aimed to assess knowledge and attitude of undergraduate medical students toward epilepsy. Methods:A 35-items standardized questionnaire was self-administered to 320 students between December 2020 and February 2021 with a recorded response rate of 61.8%. Google form was used to collect the data. The data was analyzed using R software.Results: Overall, our findings showed a negative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…13,14 Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students. [15][16][17] One study from Burkina Faso reported witchcraft as a cause of epilepsy. 18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students. [15][16][17] One study from Burkina Faso reported witchcraft as a cause of epilepsy. 18 However, there have been few available reports on misconception intervention and stigma reduction studies, especially in Sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Misconceptions, cultural beliefs, and stigmatization of epilepsy have been reported in different parts of the world; from western countries, Asian countries, and elsewhere 13,14 . Studies showed evidence of misconceptions, myths, and beliefs among different educated populations starting from school teachers as well as university students 15–17 . One study from Burkina Faso reported witchcraft as a cause of epilepsy 18 .…”
Section: Introductionmentioning
confidence: 99%